Kajian Semiotika dalam Kumpulan Puisi Gazal Hamzah Karya Marhalim Zaini - Lesi Mardiana; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Literary works describe various phenomena that occur in society. In which there are elements of semiotics namely Icons, Indexes and Symbols. In the Collection of Poetry Gazal Hamzah by Marhalim Zaini contains many semiotic elements such as icons, indexes, and symbols and the works produced have a lot of relationships between signifiers (text) and signifieds (context) related to icons, indexes and symbols. The research approach used is a qualitative approach. The method used is descriptive method. The results of this study are that in the Collection of Poetry of Gazal Hamzah by Marhalim Zaini there are still many icons, indexes and symbols. In the entire collection of Gazal Hamzah's poems by Marhalim Zaini, semiotics is used to convey meaning through the use of icons, indexes, and symbols. This research helps understand how poets use semiotic elements to create effects and explore the themes raised in the literary work. Semiotics opens the door to understanding language and the meaning hidden behind words, thereby enriching the experience of reading and enjoying Gazal Hamzah's poetry.